Effects of exercise programmes on pain, disease activity and function in ankylosing spondylitis: A meta‐analysis of randomized controlled trials. (11th August 2020) - Hu, Xinmiao; Chen, Jialing; Tang, Wenjuan; Chen, Wenjian; Sang, Yan; Jia, Lina
Abstract: Background: To evaluate the effects of exercise programmes on pain, function and disease activity in patients with ankylosing spondylitis (AS). Materials and methods: We searched PubMed, Embase, CNKI and Wanfang from inception to February 2020. Randomized controlled trials comparing exercises with nonexercise interventions in AS patients were applied. Studies that assessed the visual analogue scale (VAS) pain score, the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), the Bath Ankylosing Spondylitis Functional Index (BASFI), C‐reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were included. Outcomes of home‐based exercise intervention were also reported independently. Results: Ten studies met the inclusion criteria in all, including 534 patients (278 exercise, 256 control). Compared with the nonexercise group, exercise group had statistically significant improvements in pain (weighted mean difference [WMD]: −1.02 [95% CI: −1.50 to −0.55]) ( I 2 : 31%, P <.0001), BASDAI (WMD: −0.85 [95% CI: −1.09 to −0.61]) ( I 2 : 20%, P <.00001), and BASFI (WMD: −0.66 [95% CI: −0.95 to −0.38]) ( I 2 : 0%, P <.00001), but not in CRP and ESR. What's more, home‐based exercise programmes had positive impacts on BASFI, BASDAI and pain. Conclusions: For patients with AS, exercise programmes improve pain, function and disease activity. To confirm the results, more well‐designed randomized controlled trials with large number of patients are required.